Implementation of the Green Open Space Policy Regarding the Provision and Arrangement of Kaombona City Forest Areas, Manikulore Koľa Palu City - Rafiuddin; Sitti Aminah; Andi Sahri Alam; Tri Wahyuni Dyah Wulandari (Jurnal Penelitian Pendidikan IPA, 2024)
This research was conducted to look at implementing the Green Open Space Policy regarding the Provision and Arrangement of City Forest Areas. Based on the research results, the Provision and Arrangement of RĽH in the Kaombona City Forest Area is based on planning, analysis, design, implementation, and maintenance. In the Implementation of the Policy for Providing and Arranging Green Open Space in the City Forest Area of ​​Mantikuloie District, Palu City, the development of the City Forest has been very beneficial for urban areas as well as maintaining environmental sustainability and making it clean. However, the provision and arrangement activities are still 20% complete from the Masterplan concept which is considered to have still deficiencies including the design, implementation, and maintenance processes, namely the facilities and services of the Kaombona City Forest which are currently still under construction, apart from the play area buildings, not all road access has been built, and there are still many buildings that have not been completely built, some roads have not been asphalted, street lighting is inadequate and there are many more sports and recreation facilities that have not been completed.